Податки і трансакційні витрати у будівельній сфері - Сердюк, Т. В.; Лавровська, І. В. (Ways to Improve Construction Efficiency, 2013)
These figures ease of paying taxes in different countries; considered and include transaction costs, taxes; investigated the cost of compliance for companies with regard to their annual income.